1989
DOI: 10.1507/endocrj1954.36.845
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Role of Endogenous Digitalis-Like Substance in the Regulation of Circadian Changes in Urinary Electrolyte Excretion in Man.

Abstract: The urinary volume (U.V.), Na excretion (UNaV) and K excretion (UKV) have been reported to show a circadian rhythm in man, but the mechanism of this rhythm has not been made clear. To investigate how atrial natriuretic peptide (ANP) and endogenous digitalis-like substance (DLS) participate in the circadian change in urinary electrolyte, the circadian changes in ANP and DLS (digoxin-like immunoactivity: DLI, Na-K-ATPase inhibitor: ATPI, ouabain binding inhibitor to Na-K-ATPase: OBI) were evaluated in 5 normal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Previous studies have suggested that food intake is not an important contributor to the circadian rhythm. 33, 40, 41 In the present study, the variation observed in the overall mean values of hourly urinary Na/K ratios were not likely explained by postprandial surges. Thus, it can be inferred that food intake was irregularly reflected in urinary Na and K excretions, and the fluctuation in overall mean hourly urinary Na/K ratios is mainly related to something other than food intake, for example, hormonal factors.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Previous studies have suggested that food intake is not an important contributor to the circadian rhythm. 33, 40, 41 In the present study, the variation observed in the overall mean values of hourly urinary Na/K ratios were not likely explained by postprandial surges. Thus, it can be inferred that food intake was irregularly reflected in urinary Na and K excretions, and the fluctuation in overall mean hourly urinary Na/K ratios is mainly related to something other than food intake, for example, hormonal factors.…”
Section: Discussionsupporting
confidence: 44%
“…23, 24 However, the overall trend remains unknown. Previous studies have examined fluctuations in Na and K excretion by means of experimental trials in isolated unrealistic circumstances, 27, 28, 29 chronobiological assessments, 30, 31 protocols requiring compulsory urine sampling at specific intervals, 29, 31, 32, 33, 34, 35, 36 or experiments requiring urine withdrawal. 37, 38, 39 However, the findings of such studies are not easy to translate into clinical values in terms of obtaining insight into daily dietary behavior.…”
Section: Introductionmentioning
confidence: 99%
“…EOLS, which is released in response to volume expansion, inhibits Na -K -ATPase activity in blood vessels (22). The plasma Na -K -ATPase inhibiting activity has a diurnal rhythm, being high in the evening, and correlates positively with urinary sodium excretion in healthy subjects (23). These studies suggest that EOLS might be associated with diurnal BP variation through the diurnal rhythm of urinary sodium excretion.…”
Section: Discussionmentioning
confidence: 72%
“…Our date showed a lower daytime Na/K ratio in spot urine than Na/K ratio throughout the 24-h, which was consistent with the results [ 29 ] and lower Na/K ratio was also observed in the morning and afternoon than in the evening and overnight [ 30 ]. Previous studies suggested that food intake was not a significant contributor to the circadian rhythm in sodium and potassium excretion [ 31 , 32 ] while hormonal factors were mainly related to the fluctuation. The excretion of renal sodium and potassium was under the control of hormones, such as aldosterone [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%